Evaluation Of the Al-Quran Hafidz Program in Senior High School - Baidowi, Ach.; Eletmany, Mohamed R.; Alghifari, T. M.; Rohim, Moh. Abdur (STAI Publisistik Thawalib Jakarta, 2025)
The Tahfizh program at Senior High School Darul Quran Al-Wafa is effective but not yet optimal. This study evaluates the context, input, process, and product aspects to improve the quality and effectiveness of the program's implementation. The study uses the CIPP evaluation model, with data collected through observations, interviews, and documentation, and analyzed using triangulation to ensure data validity. The results show: (1) Context evaluation: The Tahfizh program aims to produce a generation that memorizes, reads according to tajwid, and practices the teachings of the Quran, although there are challenges in achieving memorization targets and differences in students' abilities. (2) Input evaluation: The Tahfizh program includes qualified teacher competencies, variations in students' memorization abilities, a flexible curriculum, and adequate supporting facilities. (3) Process evaluation: The Tahfizh program includes structured learning implementation with flexible time, motivational challenges, boredom, and insufficient rest time, with efforts for improvement through evaluations and more engaging approaches. (4) Product evaluation: The Tahfizh program shows positive impacts on memorization ability, religious understanding, and character development, although memorization targets have not been fully achieved, with recommendations for improvement and enhancement. Conclusion: The school's flagship tahfidz program with regular evaluations is fully supported by the school.